2020
DOI: 10.1002/phar.2439
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Clinical Diagnostics and Testing Technology

Abstract: Given the global nature of the coronavirus disease 2019 (COVID‐19) pandemic, the need for disease detection and expanding testing capacity remains critical priorities. This review discusses the technological advances in testing capability and methodology that are currently used or in development for detecting the novel coronavirus. We describe the current clinical diagnostics and technology, including molecular and serological testing approaches, for severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 65 publications
(73 reference statements)
1
95
0
3
Order By: Relevance
“…However, we have demonstrated that relying only on the detection of the IgG antibody titer for diagnostic purposes led to false negative results in several cases, most likely with samples obtained during the rather early phases of an immune response. We have shown, that the inclusion of additional immunoglobulin classes further increases the assay sensitivity and should be considered a valuable asset during the selection process of a diagnostic assay, a notion also argued already by others [ 19 , 20 ]. In addition, also the parallel analysis of more than one SARS-CoV-2 antigen for serological characterization – as demonstrated by the Genspeed COVID-19 assay – might proof beneficial for increasing diagnostic performance.…”
Section: Discussionsupporting
confidence: 56%
“…However, we have demonstrated that relying only on the detection of the IgG antibody titer for diagnostic purposes led to false negative results in several cases, most likely with samples obtained during the rather early phases of an immune response. We have shown, that the inclusion of additional immunoglobulin classes further increases the assay sensitivity and should be considered a valuable asset during the selection process of a diagnostic assay, a notion also argued already by others [ 19 , 20 ]. In addition, also the parallel analysis of more than one SARS-CoV-2 antigen for serological characterization – as demonstrated by the Genspeed COVID-19 assay – might proof beneficial for increasing diagnostic performance.…”
Section: Discussionsupporting
confidence: 56%
“…Although the diagnosis of COVID-19 relies on the detection of the SARS-CoV-2 RNA by Real-Time Reverse Transcriptase (RT)–PCR ( 4 , 12 , 13 ), here only a few endodontists were using it as their patient screening technique. No endodontist participant requested chest X-ray for COVID-19 screening in their dental practice, although chest X-ray might show patchy shadows and ground-glass opacity in the lung ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 disease is caused by the novel coronavirus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2, formerly known as 2019-nCoV) ( 4 ). The most commonly reported routes of SARS-CoV-2 transmission are inhalation or direct inoculation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…These tests are most often performed in large labs at commercial diagnostic facilities or academic centers. Specimens from individuals with suspected infection must, therefore, be sent to these labs, increasing both the time and coordination requirements [ 65 ]. Thus, different alternatives have been proposed for improvements in the performance of the RT-qPCR assay with the use of high throughput platforms (or systems), which involve an automated workflow to enable high throughput testing with minimal hands-on time, and still offering fast, reliable results [ 66 ].…”
Section: Nucleic Acid-based Testsmentioning
confidence: 99%